Analysis of PWM- and MPPT-solar charge controller efficiency by simulation. Issue 2 (June 2021) - Fianti,; Perdana, AY; Astuti, B; Akhlis, I
Abstract: Indonesia is a tropical country having high potential of solar energy. In contrary, solar irradiation is varied due to obstruction of the sun by clouds, the difference of intensity of the sun all day, the occurrence of clouds during the rainy season, and the presence of fog in certain areas making it irradiation rate of solar light thus causing the solar cell output power to be varied and not optimum. Therefore, control device is needed to stabilize output power from solar cell, called solar charge controller. This study aims were to measure its efficiency values and compare two type of SCC, i.e. PWM and MPPT. Solar cell voltage and current were obtained by measuring those parameters manually from solar panel on the field and analysed by MATLAB. The data showed that power value, voltage, and influx produced by MPPT were 6.23 W, 12.39 V, 4.9 A and PWM were 6.04 W, 12.16 V, 4.8 A. Average efficiency value of PWM was 172% and MPPT was 177%. Data analysis revealed that MPPT have superiority accorded to its power value, voltage, and influx compared to PWM. By this, MPPT was preference application onto solar harvesting system.